Assessing Fiscal Sustainability for SAARC and IMT-GT Countries - Syed Munawar-Shah; Mariani Abdul-Majid; Syed Hussain-Shah (Romanian Journal of Fiscal Policy (RJFP), 2014)
This study examines the fiscal sustainability of SAARC and Asian Growth-Triangle countries using Fisher and IPS tests of panel unit root and Pedroni test of panel cointegration. The tests are applied to the relationships, in terms of GDP ratios, between, i) the debt and primary surplus, and ii) government expenditure and revenues. Both models show consistent results suggesting that fiscal policy for the low-income countries is sustainable whereas it may not be sustainable for the high-income countries. This also indicates that the fiscal policy can be sustainable (non-sustainable) even for the debt above (below) 60 percent of the GDP.
Keywords: E62; H63; 330; Debt; Fiscal Policy; Sustainability; Panel Unit Root; Panel Cointegration